2002
DOI: 10.1074/jbc.m209599200
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Kir3.1 Subunit to the Muscarinic-gated Atrial Potassium Channel IKACh

Abstract: The muscarinic-gated atrial potassium (I KACh ) channel contributes to the heart rate decrease triggered by the parasympathetic nervous system. I KACh is a heteromultimeric complex formed by Kir3.1 and Kir3.4 subunits, although Kir3.4 homomultimers have also been proposed to contribute to this conductance. While Kir3.4 homomultimers evince many properties of I KACh , the contribution of Kir3.1 to I KACh is less well understood. Here, we explored the significance of Kir3.1 using knock-out mice. Kir3.1 knock-out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 36 publications
2
91
1
Order By: Relevance
“…As was shown previously (21,23), the heart rate of Girk4 −/− mice was significantly higher than the heart rate of WT controls, and these mice presented normal AV conduction and response to injection of atropine and propranolol (Fig. 1D).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…As was shown previously (21,23), the heart rate of Girk4 −/− mice was significantly higher than the heart rate of WT controls, and these mice presented normal AV conduction and response to injection of atropine and propranolol (Fig. 1D).…”
Section: Resultssupporting
confidence: 55%
“…Two subunits of the G-protein activated inwardly rectifying K + channels (GIRK1 and GIRK4) of the GIRK/ Kir3 subfamily assemble as heterotetramers to form cardiac I KACh channels (22). Indeed, both Girk1 −/− and Girk4 −/− mice lack cardiac I KACh (20,21,23). We recently showed that silencing of the hyperpolarization-activated current "funny" (I f ) channel in mice induces a complex arrhythmic profile that can be rescued by concurrent genetic ablation of Girk4 (24).…”
Section: Significancementioning
confidence: 99%
“…GIRK1 or GIRK4 knockout mice exhibit slightly elevated resting heart rates (Bettahi et al, 2002). Atomoxetine and reboxetine are associated with modest increases in heart rate (Hajós et al, 2004;Simpson and Plosker, 2004) and tachycardia in cases of toxicity (LoVecchio and Kashani, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Mice were housed in a temperaturecontrolled room on a 12 hr light/dark cycle, with food and water available ad libitum. The generation of GIRK1 knock-out (Bettahi et al, 2002), GIRK2 knock-out (Signorini et al, 1997), GIRK3 knock-out (Torrecilla et al, 2002), and GIRK2/GIRK3 double knock-out (Torrecilla et al, 2002) mice was described previously. The GIRK null mutations were backcrossed through at least nine rounds against the C57BL/6 mouse strain before initiating this study.…”
Section: Methodsmentioning
confidence: 99%